Fractional nonlocal impulsive quasilinear multi-delay integro-differential systems - Debbouche, Amar (Advances in difference equations, 2011)
In this article, sufficient conditions for the existence result of quasilinear multi-delay integro-differential equations of fractional orders with nonlocal impulsive conditions in Banach spaces have been presented using fractional calculus, resolvent operators, and Banach fixed point theorem. As an application that illustrates the abstract results, a nonlocal impulsive quasilinear multi-delay integro-partial differential system of fractional order is given. AMS Subject Classifications . 34K05, 34G20, 26A33, 35A05.